2008
DOI: 10.1128/aem.02254-07
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Structure and Transferability of Tn 1546 -Like Elements in Enterococcus faecium Isolates from Clinical, Sewage, and Surface Water Samples in Iran

Abstract: The molecular structure and transferability of Tn1546 in 143 vancomycin-resistant Enterococcus faecium (VREF) isolates obtained from patients (n ‫؍‬ 49), surface water (n ‫؍‬ 28), and urban and hospital sewage (n ‫؍‬ 66) in Tehran, Iran, were investigated. Molecular characterization of Tn1546 elements in vanA VREF was performed using a combination of restriction fragment length polymorphism analysis and DNA sequencing of the internal PCR fragments of vanA transposons. Long-PCR amplification showed that the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…The population structure determined for Polish VR Efm VanA closely resembled these of hospital-associated E. faecium in other countries. High diversity of STs/MTs is consistent with the presence of polyclonal hospital population of E. faecium that subsequently acquires vancomycin resistance determinants [13, 14]. The vast majority of isolates grouped into hospital lineage 17/18, mostly represented by STs 17, 117, 18, 132, 202 and lineage 78, which included STs 78, 192 and 412.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The population structure determined for Polish VR Efm VanA closely resembled these of hospital-associated E. faecium in other countries. High diversity of STs/MTs is consistent with the presence of polyclonal hospital population of E. faecium that subsequently acquires vancomycin resistance determinants [13, 14]. The vast majority of isolates grouped into hospital lineage 17/18, mostly represented by STs 17, 117, 18, 132, 202 and lineage 78, which included STs 78, 192 and 412.…”
Section: Discussionmentioning
confidence: 84%
“…The vanA gene cluster is carried on Tn 1546 -type transposons [12], which show a significant degree of heterogeneity, associated with presence of point mutations, deletions and presence of various ISs [13, 14]. A few studies demonstrated the location of Tn 1546 on Inc18, pRUM-like, pMG1-like, and pLG1 plasmids [15, 16]; however, the knowledge of vanA -plasmids and their epidemiology is still far from being satisfactory and may differ significantly among countries.…”
Section: Introductionmentioning
confidence: 99%
“…[3,6] Other virulence factors such as Esp and Hly have been described in both E. faecalis and E. faecium. [4,7] In continuation with our previous reports, [8,9] here we investigate the virulence factors in E. faecium isolated from clinical setting and sewage in Iran, where no such information is available.…”
Section: Introductionmentioning
confidence: 78%
“…In enterococci, differences between Tn1546-related elements from animals and humans (25,45), as well as heterogeneity in Tn1546-like elements with IS1216 insertions (46,47), have been described previously. These features has not been reported previously for S. gallolyticus subsp.…”
Section: Discussionmentioning
confidence: 62%